Pengaruh Web Based Learning terhadap Hasil Belajar Ditinjau dari Self-Directed Learning - Krida Puji Rahayu (SAP (Susunan Artikel Pendidikan), 2018)
The purpose of the research is to determine the effect of and interaction between chemistry learning with web-based learning models using moodle and blog on the cognitive learning outcomes of students class grade X on chemical bond material in terms of the self-directed learning (SDL) ability of different students. This research uses a quasi-experimental research design, namely the posttest-only non equivalent control group. Sampling is conducted applying cluster random sampling technique. The research data are student’s learning outcomes collected using the instrument in the form of objective test consisting of 35 questions related to chemical bond material with the content validity of 81.8% (very high). The reliability coefficient calculated using the KR-21 is 0.88 (valid and reliable). Test of the hypothesis is conducted by using two-wayANOVA in SPSS16 statistics program for Windows. The results of the research show that: (1) there is no difference in cognitive learning outcomes of students learning with web-based learning models using either blog or moodle media; (2) there is a difference in cognitive learning outcomes of students in terms of the self-directed learning ability of students learning either with a blog or moodle media; (3) there is an interaction of the learning model and self-directed learning ability with  cognitive learning outcomes of students.